A complex molecular landscape to drug delivery concept for achieving precise therapy in psoriasis - Krishna Yadav; Kantrol Kumar Sahu; Sucheta; Renu Yadav; Wasim Raza; Sunita Minz; Manju Rawat Singh; Deependra Singh; Madhulika Pradhan (Elsevier, 2024)
Psoriasis is a chronic autoimmune disorder that has a major effect on the quality of life for millions of people throughout the world. The pathogenesis of psoriasis has revealed intricate molecular networks and signaling pathways, opening new avenues for precision medicine. Psoriasis treatments include topical therapy, phototherapy, systemic therapies, and biologics, but achieving optimal outcomes is difficult. Despite advancements in understanding the causes of psoriasis and the development of various treatments, optimizing therapeutic outcomes remains challenging. Managing psoriasis poses challenges in terms of drug delivery and evaluation models. Novel drug delivery systems capable of navigating complex skin barriers and delivering therapeutics precisely to target cells are crucial for advancing treatment options. This article provides an inclusive overview of psoriasis, highlighting recent discoveries and potential therapeutic targets. The article emphasizes the importance of combining different modalities, such as synthetic and herbal agents, with biologics to improve efficacy. Nanocarriers show promise for targeted drug delivery in psoriasis, as they can encapsulate antipsoriatic drugs, biologics, and gene therapies, providing enhanced stability, improved tissue penetration, and precise cellular targeting. These advancements in drug delivery systems have the potential to revolutionize psoriasis treatment by maximizing efficacy while minimizing side effects. The article also discusses the commercial outcomes in psoriasis formulations, including patents related to treatment and ongoing clinical trials, which provide valuable insights into the evolving landscape of psoriasis therapeutics. These insights contribute to the evolving field of psoriasis therapeutics and offer hope for improved outcomes for patients suffering from psoriasis.